Energy-efficient outdoor air flow control in ventilation systems - A. B. Sulin; A. A. Nikitin; T. V. Ryabova; S. S. Muraveinikov; I. N. Sankina (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
A method for controlling the ventilation system flow characteristics is considered based on the forming principle an air temperature and carbon dioxide concentration predicted estimate in a room based on the changes dynamics analysis in these parameters in the supply and exhaust ducts. The expected microclimate parameters predicted assessment in real time opens up the possibility of using such elements and algorithms for controlling the ventilation and air conditioning system, which provide the required air quality with minimal energy consumption. The analysis calculates the finding probability the measured parameter inside or outside the control zone after a specified time interval. The algorithm for the control system actuators actuation for the channels of temperature and carbon dioxide concentration is presented in the block diagram form. The decision-making logic for actuating the actuators is based on the changes direction and intensity analysis in temperature and carbon dioxide concentration in the exhaust duct and the temperature difference between the supply and exhaust